SafeRouteGuard : Accident-Aware Navigation System - Garande, Anuja Garande; Kondhalkar, Omkar; Sherigar, Ayush; Rathod, Pranav; Gadhave, Manish (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
SaferRouteGuard is a novel web application designed to enhance road safety by providing real-time notifications of accident- prone zones, or "black spots," along user-input routes. This system aims to reduce the likelihood of accidents and enhance overall road safety. The research paper discusses the development, methodology, data sources, and future scope of SaferRouteGuard. In a world where transportation is a vital part of our daily lives, road safety remains a paramount concern. The alarming frequency of road accidents, their devastating consequences, and the associated economic burden demand innovative solutions that can proactively address this issue. We are proud to present a groundbreaking project that brings together technology, data analysis, and real-world impact in the form of the "Road Accident Navigation System and Minimal Accident Route Recommendation.”
Keywords: Security Issues; Mapbox Security; Openstreetmap Architecture; Challenges; Automation of Road Safety Industry; Security Zone Threats; Security Measurement Frameworks